Child militancy in Pakistan: A Human Security Challenge - Shabana Fayyaz (Journal of Political Studies, 2017)
In the wake of 9/11 Pakistan has witnessed a sharp escalation in the number of children being recruited by extremist organizations. Terrorist organizations, political factions and various other extremist groups recruit children for their own religious-political agenda within the country. According to the UNICEF, more than two million children have died in conflicts and approximately 300,000 child militants are fighting conflicts. The paper argues that national security paradigm must register human security as its key element. Children of the country are Pakistan’s real national security assets and their wellbeing will ensure a stable, prosperous and peaceful future. To deliberate more deeply into the subject the paper is divided into three inter-related parts: Part one dwells upon the genesis and nature of the child militancy in Pakistan; Part two analyzes the factors contributing to this dangerous trend of children being used as weapons of war by the non-state actors, finally; Part three focuses upon the various state approaches to deal with the issue of child militancy in the country. In conclusion few recommendations will be advanced to how reverse and slow down the challenge of child militants in present and future.